2002
DOI: 10.2172/15002143
|View full text |Cite
|
Sign up to set email alerts
|

The Stochastic Engine Initiative: Improving Prediction of Behavior in Geologic Environments We Cannot Directly Observe

Abstract: T h e S t o c h a s t i c En g i n e I n it i a t i ve : I m p r o v i n g Pr e d ic t i o n of Be h a v i o r in Ge ol o g i c En v i r on m e n t s W e C a n n o t D i r e ct l y Ob s e r v e1 4 0 z (m) -1 0 x ( m ) 0 1 0 1 0 0 -1 0 y ( m )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…Here we briefly outline the general concepts of the Bayesian MCMC methodology used in our work. For further details on its theory and application to geophysical inverse problems, see, for example, Mosegaard and Tarantola [1995], Bosch [1999], Aines et al [2002], and Ramirez et al [2005]. We begin by considering n sets of measured data { d 1 , …, d n } that each informs us in some way about the subsurface environment, and the vector m that contains the model parameters of interest, in our case the spatial configuration of K. Regarding m as a multivariate probability distribution, Bayes' Theorem can be used to update our initial state of knowledge about these parameters into a more refined state of knowledge given the available data.…”
Section: Inversion Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Here we briefly outline the general concepts of the Bayesian MCMC methodology used in our work. For further details on its theory and application to geophysical inverse problems, see, for example, Mosegaard and Tarantola [1995], Bosch [1999], Aines et al [2002], and Ramirez et al [2005]. We begin by considering n sets of measured data { d 1 , …, d n } that each informs us in some way about the subsurface environment, and the vector m that contains the model parameters of interest, in our case the spatial configuration of K. Regarding m as a multivariate probability distribution, Bayes' Theorem can be used to update our initial state of knowledge about these parameters into a more refined state of knowledge given the available data.…”
Section: Inversion Methodologymentioning
confidence: 99%
“…In recent years, a number of papers have appeared in the geophysical literature that treat the complex data integration and inversion problem for spatially distributed subsurface properties in a fully stochastic manner using Bayes' Theorem [e.g., Mosegaard and Tarantola , 1995; Bosch , 1999; Aines et al , 2002; Eidsvik et al , 2002; Ramirez et al , 2005]. Once thought computationally impractical, the results in these papers have demonstrated that with modern computational resources and state‐of‐the‐art forward simulation and sampling algorithms, such stochastic data integration is feasible for real‐world problems.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed description of the application of the MCMC approach to plume reconstruction is found in Ramirez et al [1]. Importantly, the basic approach was developed in a prior LDRD-SI proposal as described in Aines et al [2] This approach is useful for a variety of subsurface problems such as geophysical inversion, data fusion, and reservoir fluid flow monitoring (water floods, steam injection, CO 2 floods). A key advantage of the approach is that it explicitly treats the nonuniqueness inherent in geophysical inversion.…”
Section: Base Methodologymentioning
confidence: 99%
“…This tool may include multiattribute utility theory to evaluate alternatives for complicated problems with multiple objectives (e.g., Dyer et al, 1998), or might involve a stochastic approach to guide optimal sensor placement within distribution systems (e.g., Murray, 2004;Johannesson et al, 2004). Such methodologies have been successfully applied to problems including the disposition of surplus weapons grade plutonium, the siting of an electricity generation facility (Dyer et al, 1998), improved predictions of contaminant transport through geologic material (Aines et al, 2002), and improved sensor and source analysis for atmospheric dispersion problems (Johannesson et al, 2004). Additional fidelity could include the economic considerations for both (1) UCRL-/SAND2005-2/4 employing current technologies in an EWS role for water distribution systems and (2) developing emerging sensor technologies specifically for water distribution system use.…”
Section: Toward a More Detailed Sensor Down Selection Criteriamentioning
confidence: 99%